REPERCUSSIONS OF CROHN'S DISEASE IN THE PEDIATRIC PATIENT (CIPEEX, 2022)
CROHN'S DISEASE (CD) IS CHARACTERIZED BY MULTISYSTEMIC CLINICAL MANIFESTATIONS, AND ITS ONSET IS ASSOCIATED WITH ENVIRONMENTAL, GENETIC, IMMUNOLOGICAL, AND GUT MICROBIOTA FACTORS. IT IS A CHRONIC TRANSMURAL INFLAMMATION THAT CAN INVOLVE ANY PART OF THE DIGESTIVE TRACT FROM THE MOUTH TO THE ANUS, MAINLY FOUND IN THE ILEUM, CECUM, AND COLON. CD CAN INVOLVE THE SMALL INTESTINE AND/OR THE COLON AND/OR THE PERIANAL REGION, AND CAN BE CHARACTERIZED AS INFLAMMATORY, STENOSING, AND PENETRATING/FISTULIZING FORMS, WHICH CAN MANIFEST IN COMBINATION OR EVOLVE FROM ONE PATTERN TO ANOTHER. ALSO, ALTHOUGH LESS FREQUENTLY, CD CAN INVOLVE THE UPPER DIGESTIVE TRACT, AFFECTING THE MOUTH, ESOPHAGUS, STOMACH, AND DUODENUM. UP TO 30% OF PATIENTS HAVE SYMPTOM ONSET IN THE PEDIATRIC AGE GROUP, WHICH ENTAILS THE NEED FOR AN EFFECTIVE DIAGNOSIS AND INDIVIDUALIZED FOLLOW-UP WITH ATTENTION TO THE REPERCUSSIONS ON THE LIVES OF AFFECTED CHILDREN AND ADOLESCENTES -. INTEGRATIVE LITERATURE REVIEW, THROUGH THE ANALYSIS OF 17 ORIGINAL ARTICLES, PUBLISHED BETWEEN 2012 AND 2022, AIMING TO ANSWER THE QUESTION: "WHAT ARE THE REPERCUSSIONS OF CROHN'S DISEASE IN CHILDHOOD AND ADOLESCENCE?". SHORT-TERM REPERCUSSIONS WERE FOUND, SUCH AS THE WIDE RANGE OF SYMPTOMS INVOLVING MAINLY ABDOMINAL PAIN, HIGH INCIDENCE OF COMPLICATIONS LEADING TO THE IMMINENT NEED FOR SURGICAL INTERVENTION, AND REDUCED QUALITY OF LIFE, INCLUDING PSYCHO-EMOTIONAL ASPECTS, SCHOOL, SOCIAL IMAGE, AND DAMAGES ARISING FROM CLINICAL MANIFESTATIONS, IN ADDITION TO THE NEED FOR DIETARY MODIFICATIONS. ACCORDINGLY, THE LONG-TERM REPERCUSSIONS INCLUDED GROWTH RETARDATION AND SIDE EFFECTS OF PHARMACOLOGICAL TREATMENT. THE MULTIFACTORIAL NEGATIVE REPERCUSSIONS AND THE GREATER DEVELOPMENT OF COMPLICATIONS OF CROHN'S DISEASE IN PEDIATRIC PATIENTS, AS WELL AS THE DIFFICULTIES IN TREATMENT, MAKE IT ESSENTIAL TO IMPLEMENT MEASURES TO REDUCE THE INCIDENCE OF THE DISEASE, TO ENCOURAGE ROUTINE CONSULTATIONS, AND TO PERFORM A COMPREHENSIVE AND INDIVIDUALIZED EVALUATION OF THE PEDIATRIC PATIENT, AVOIDING THE CRITICALITY OF CROHN'S DISEASE AND AIMING FOR CLINICAL REMISSION.
Keywords: crohn’s disease; pediatrics; child